The transcriptome of Litopenaeus vannamei in zoea larvae and adults infected by Vibrio parahaemolyticus - Chen, Nanxiong; Jin, Jiaojiao; Chen, Yibin; Hu, Yicheng; Shen, Yuchun; Li, Sedong (Frontiers in Marine Science, 2023)
Introduction The rapid development of the Litopenaeus vannamei industry largely depends on the acquisition of high-quality larvae. Shrimp larval development is a unique metamorphic process that results in mortality due to disease vulnerability. Currently, studies on innate immunity in shrimp are mainly focused on the adult stage, but little has been done on innate immunity in larvae. Methods In this study, utilizing a high-throughput Illumina sequencing approach, we compare the transcriptome of L. vannamei Zoea larvae and adults infected by Vibrio parahaemolyticus. Results A total of 487,887,650 high quality reads were obtained, assembled, and aggregated into 23,802 genes, among which 3315 were identified as differentially expressed genes. Then GO term enrichment analysis, KEGG pathway enrichment analysis and functional gene analysis were performed. We found that pathways that are involved in the innate immune response, such as mTOR signaling pathway, MAPK signaling pathway, and Notch signaling pathway, were more enriched in the Zoea stage compared to the adult stage, suggesting that innate immunity against Vibrio vulnificus may exist during the Zoea larvae stage. Discussion were more enriched in the Zoea stage compared to the adult stage, suggesting that innate immunity against Vibrio vulnificus may exist during the Zoea larvae stage. These findings will provide useful information for the study of innate immunity in shrimp larvae.